Stress and recovery in sports: Effects on heart rate variability, cortisol, and subjective experience; International Journal of Psychophysiology; Vol. 143 - Vacher Ph. Philippe; Filaire E. Edith; Mourot L. Laurent; Nicolas M. Michel (2019, 2019)
Title screen